2018
DOI: 10.4103/sajc.sajc_55_17
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcomes in anaplastic gliomas: An institutional experience

Abstract: Background:There is lack of clear evidence and treatment guidelines for anaplastic gliomas (AGs) with very few studies focusing exclusively on these patients. The aim of the study was to analyze the clinical profile and survival in these patients.Materials and Methods:Patients of AGs treated with radiation and concurrent ± adjuvant chemotherapy from January 2010 to December 2015 were analyzed. Statistical analysis was done using SPSS version 20 software.Results:A total of 100 patients were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…In our study, patients treated with adjuvant chemoradiation followed by adjuvant temozolomide showed better outcomes. Deepthi Valiyaveettil [19] et al's study also showed that concurrent and adjuvant temozolomide patients had better survival rates. Emory McTyre [20] that had1p/19q co-deleted patients and is for RT followed by PCV versus TMZ concurrent with RT followed by adjuvant TMZ versus TMZ alone.…”
Section: Factors Affecting the Outcomementioning
confidence: 92%
“…In our study, patients treated with adjuvant chemoradiation followed by adjuvant temozolomide showed better outcomes. Deepthi Valiyaveettil [19] et al's study also showed that concurrent and adjuvant temozolomide patients had better survival rates. Emory McTyre [20] that had1p/19q co-deleted patients and is for RT followed by PCV versus TMZ concurrent with RT followed by adjuvant TMZ versus TMZ alone.…”
Section: Factors Affecting the Outcomementioning
confidence: 92%
“…The prognosis of this type of tumor is rather poor, with a mean 5-year survival of 28.6% (11), which increases to 41.8% if the patient receives adjuvant chemo-and radiotherapy (12). For overall survival, positive prognostic factors have been described: age (<41), isocitrate dehydrogenase mutation, radical resection and Karnofsky performance status of at least 90% (13), however, another source states a positive effect of Karnofsky performance status of at least 70% (14). In the latter case (Karnofsky performance status of 70%), our patient would have all of the positive factors mentioned above.…”
Section: Case Reportmentioning
confidence: 99%
“…Other studies showed that patients with Karnofsky Performance Score (KPS) of ≥70 have a significantly better 5-year OS(Overall Survival) as compared to those with KPS <70 (33%) . The use of adjuvant temozolomide (TMZ) shows longer 5-year OS compared to 36% in patients who did not receive adjuvant chemotherapy (20) Unfortunately, we cannot get a general conclusion about the epidemiological characteristics of anaplastic gliomas on the entire territory of the Republic of Serbia, due to the lack of precise unified data. Radical surgery, which is not an end in itself, is one of the basic prognostic factors.…”
Section: Discusionmentioning
confidence: 99%